OPTIMALISASI DIGITAL MARKETING SEBAGAI STRATEGI INOVATIF PEMASARAN UNTUK MENINGKATKAN AKSES PASAR UMKM ANYAMAN PANDAN - susetyo, aris; Galuh Puspita Dewi; Heni Riyanti; Siti Alfiyah; Fina Resti Rahmadhani (PT. Karya Inovatif Nusantara, 2025)
This community service aims to identify the potential and challenges faced by pandan weaving SMEs in marketing their products, as well as the importance of optimizing digital marketing as an innovative strategy to improve market access. Based on preliminary surveys, the pandan weaving products produced by Kampoeng Anyaman still face marketing challenges, limited product creativity, and dependence on inconsistent pandan raw material supply. Although the products have been sold both locally and internationally, digital marketing has not been maximized. Therefore, optimizing the use of digital platforms such as social media, e-commerce, and websites is crucial to expand market reach, build a stronger brand, and improve marketing efficiency. This study concludes that by utilizing digital technology, pandan weaving SMEs can increase product visibility, directly interact with consumers, and strengthen competitiveness in both local and international markets. Thus, the implementation of appropriate digital marketing strategies will help SMEs survive and thrive in an increasingly competitive market.